Bodily experiences of patients diagnosed with anorexia nervosa during treatment with the body monochord - Fendel, Uta; Sandler, Hubertus; Papachristou, Christina; Voigt, Barbara; Rose, Matthias; Klapp, Burghard Friedrich (My University, 2018)
This study explored the subjective bodily experiences of patients with a diagnosis of anorexia nervosa (AN) during vibro-acoustic stimulation sessions with the Body Monochord (BoMo), a body sound treatment instrument. A total of 20 female patients diagnosed with AN received two BoMo treatments. Subsequent to the treatments, semi-structured interviews were conducted. Analysis was conducted using Grounded Theory. The following main categories were identified: differentiated perception, focussed attention, emergence of bodyrelated feelings, emergence of emotions, emergence of thoughts, emergence of inner images, relaxation, spatial and temporal experience, new bodily experiences and self-reflection. The subjective experiences during the BoMo treatment were independent of patient body shape and weight, were not exclusively focussed on usual illnessrelated body problem areas like the belly and the thighs and had both positive and negative connotations. New therapeutic approaches that are suited to handling and integrating new bodily experiences in patients diagnosed with AN may develop from these observations. Due to the variety of issues that emerge during the treatments BoMo might present a meaningful extension to verbal psychotherapy.
A modified grounded theory approach
Keywords: Gesundheit; Medizin; Körper; 610; Anorexie; Grounded Theory